Mixed steel deck system and its applications in civil construction (Research, Society and Development, 2019)
The concept of a mixed slab or cooperative slab emerged in the United States in the 1950s and has since become widely used, clearly in multi-story metal buildings. Already in Brazil, began to be diffused in the 1970s by the company Robtek (association between the American company Robertson and the Brazilian company Tekno). The slab steel deck or cooperative or mixed slab as it is also known, is a technique used in the construction of slabs in buildings of various sizes. A slab composed basically of galvanized steel sheets or tiles and a layer of concrete. The use of slab with cooperative forms can be considered in industrial buildings projects; in slabs of schools, roads; hospitals and public bodies; airport terminals, walkways or bridges; cinemas and shopping malls; multi-story office buildings. They can be used in concrete structures as well as metal structures. This type of slab is being used a lot, because the speed of execution is much greater, one of the main characteristics said by specialists of the area. In commercial, residential or industrial works, this type of slab is generally applied in works where there is short delivery and the need to rationalize construction processes.